Medical education, simulation and uncertainty. (6th January 2020) - Scott, Ashley; Sudlow, Mark; Shaw, Emily; Fisher, James
Summary: Background: Foundation doctors often feel underprepared to cope with uncertainty, particularly in an acute setting. Simulation is an established method for teaching about the management of acutely unwell patients, yet simulated cases are often simplified to ensure that a given learning outcome is reached. This approach may present learners with challenges in clinical practice when more complex nuanced cases are encountered. We explored final‐year medical students' perceptions of clinical uncertainty when facing an 'authentically' complex simulated patient. Methods: We adapted a simulation scenario in an attempt to replicate clinical uncertainty. The simulated patient had a confused history, only mildly deranged physiology, no current clear diagnosis and no diagnostic investigations yet available. Students engaged in debriefs facilitated by the researchers, which employed advocacy and enquiry to help students to reflect on their simulations (the 'Diamond Approach'). These were transcribed, coded and analysed thematically. Results: Students found the 'uncertainty' simulation more challenging than a 'typical' simulation. Students found it disheartening when the patient had no clear diagnosis and expected 'an answer'. Students described task fixation and/or inaction in the face of uncertainty, struggled to identify appropriate times to seek senior support and were confused about their role in managing complex cases. Discussion: We propose that this session prompted valuable discussion amongst students about how to react to clinical uncertainty. Students generally perceived the simulation as being useful. Affording space for reflection and allowing students to consider strategies for coping with uncertainty may help them when managing complex cases as Foundation doctors.